The Photon-Drag Effect in Cylindrical Quantum Wire with an Infinite Potential for the Case of Electrons – Acoustic Phonon Scattering - Hoang Van, Ngoc; Nguyen, Nhan Vu; Dinh, Vuong Quoc (VNU Journal of Science: Mathematics - Physics, 2017)
Abstract - The photon - drag effect with electrons – acoustic phonon scattering in cylindrical quantum wire with an infinite potential is studied. With the appearance of the linearly polarized electromagnetic wave, the laser radiation field and the dc electric field, analytic expressions for the density of the direct current are calculated by the quantum kinetic equation. The dependence of the direct current density on the frequency of the laser radiation field, the frequency of the linearly polarized electromagnetic wave and the temperature of the system is obtained. The analytic expressions are numerically evaluated and plotted for a specific quantum wire, GaAs/AlGaAs. The difference of the density of the direct current in quantum wires from quantum well and bulk semiconductor is due to potential barrier and characteristic parameters of system. These results are for every temperature and are new results.